Bases of Biquadratic Polynomial Spline Spaces over Hierarchical T-Meshes (Journal of Computational Mathematics, 2018)
Basis functions of biquadratic polynomial spline spaces over hierarchical T-meshes are constructed. The basis functions are all tensor-product B-splines, which are linearly independent, nonnegative and complete. To make basis functions more efficient for geometric modeling, we also give out a new basis with the property of unit partition. Two preliminary applications are given to demonstrate that the new basis is efficient.
Keywords: Spline spaces over T-meshes; CVR graph; Basis functions.